Investment Support for the Innovative Transformation of Construction Industry Enterprises - Maksiuta, Anton (Ways to Improve Construction Efficiency, 2024)
The article explores the role of investment support as a key driver of the innovative transformation of construction industry enterprises. It emphasizes the importance of attracting financial resources for the implementation of modern technologies, modernization of production processes, enhancement of management efficiency, and sustainable development. The study analyzes current approaches to investment policy formation in construction companies, as well as the structure, sources, and dynamics of investment flows under market economy conditions. Particular attention is paid to the influence of investments on the innovation activity of construction enterprises, especially regarding the introduction of energy-efficient technologies, digital project management tools, and production automation. The article identifies the main barriers to effective investment in innovation, such as limited access to financing, high technological risks, and regulatory challenges. Based on the research findings, practical recommendations are proposed to improve investment planning tools, strengthen innovation capacity, and enhance strategic development frameworks. The outcomes of the study can be useful for business leaders, investors, and policymakers in designing effective investment strategies and regulatory instruments to stimulate innovation in the construction sector.